Trait Aggressiveness and Aggressive Behavior in the Context of Provocation and Inhibition. Issue 5 (27th May 2016) - Sherrill, Andrew M.; Magliano, Joseph P.; Rosenbaum, Alan; Bell, Kathryn M.; Wallace, Patricia S.
ABSTRACT: Aggressive behavior often occurs despite salient cues within the immediate environment that indicate aversive consequences will likely follow. Prior research has shown high trait aggressiveness to be related to sensitivity to situational provocation; however, little research has examined whether it is also related to insensitivity to situational inhibitors. This study examines the relationship between trait aggressiveness and aggressive behavior in a provocative context with, and without, an unambiguous inhibitory stimulus. Prior to experiencing provocation and being afforded the opportunity to retaliate, participants who varied in trait aggressiveness were explicitly given (or not given) an instruction that aggressive behavior might lead to aversive consequences and, thus, one should not behave aggressively. Findings revealed that without the instruction, those higher in trait aggressiveness exhibited steeper increases in aggressive responding as provocation increased. In the group that received the instruction, trait aggressiveness was unrelated to aggressive responding at all levels of provocation.